Pengaruh Pengaruh Kualitas Produk Dan Harga Terhadap Minat Beli Ulang Konsumen Smartphone Xiaomi Di Kota Bandung - Anjellia, Raden Roro Dewita; Herawati, Siti (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
The purpose of this study is to analyze the effect of product quality and price on the repurchase interest of Xiaomi Smartphone consumers in Bandung City. In this study, the author used a quantitative approach. Determination of samples in the study using purposive sampling techniques which included nonprobability sampling involving 90 respondents. Primary data is obtained from questionnaires by sharing them online. This questionnaire has been tested for validity & reliability. The data have also passed the classical assumption test and meet the requirements for multiple regression tests to generate hypotheses. The results of this study state that product quality has a positive and significant effect on the repurchase interest of Xiaomi Smartphone consumers in Bandung City, price has a positive and significant effect on the repurchase interest of Xiaomi Smartphone consumers in Bandung City , product quality and price have a positive and significant effect simultaneously on the repurchase interest of Xiaomi Smartphone consumers in Bandung City .